Pemodelan Dan Simulasi Pengeringan Jagung Pipilan Dalam Pengering Rotari Tumpukan - Leopold Oscar Nelwan; I Nengah Suastawa; Sulikah . (PERTETA, 2008)
A mathematical model of shelled corn drying has been developed in order to simulate the distribution of drying air temperature and humidity as well as the grain moisture content in a rotary bed dryer. The model was based on heat and mass balance of cylindrical packed bed of grain with airflow passing through the bed. Whenever the air relative humidity is higher than the equilibrium moisture content, it is assumed the condensation process will be occurred. Finite difference method with Euler scheme was used to perform the computation. The result showed that the model developed can predict the distribution ofgrain temperature and moisture content. The simulation conducted showed that there would be a wide variation ofmoisture content and temperature if mixing was not applied during the drying process. Mixing was significantly reduced the moisture content variation until a maximum of 0.8% w.b.Keywords: rotary bed drying, mathematical model, simulation, corn dryingDiterima: 5 Februari 2008; Disetujui: 26 Juni 2008